PENGARUH RASIO KEUANGAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2021-2024 - Nurmia; Sahrullah, SE.,M.Ak; Asriani Hasan, SE., M.Sc (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of the Current Ratio and Return on Assets on Earnings Management. This research is a quantitative study using secondary data in the form of financial statements. The population in this study consists of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. The sample was obtained using purposive sampling, resulting in 108 units of data. Multiple linear regression analysis, using IBM SPSS 25, was employed to test the hypotheses. The results indicate that the Current Ratio has a positive and significant impact on earnings management, and the Return on Assets also has a positive and significant effect on earnings management.